Semen characteristics of transwomen referred for sperm banking before sex transition: a case series. (1st October 2014) - Hamada, A.; Kingsberg, S.; Wierckx, K.; T'Sjoen, G.; De Sutter, P.; Knudson, G.; Agarwal, A.
Summary Transwomen (TW) can now turn to cryopreserve spermatozoa before gender reassignment (GR). The objective is to assess semen quality of TW and evaluate adequacy for assisted reproduction technology (ART). Pre‐freezing (PF) and post‐thaw (PT) semen parameters of 2 and PF data of 27 TW who were referred for sperm banking in Cleveland Clinic/USA and Ghent Center/Belgium, before GR, were retrospectively analysed. The study period was between February, 2003 and October, 2011. We also evaluated adequacy of 24‐h PT data for ART. PF data of 29 TW, mean age of 28.9 years, showed high incidence of oligozoospermia (27.58%), asthenozoospermia (31%) and teratozoospermia (31%). Mean sperm concentration was 46.9 × 106/ml, mean per cent motility was 42.9 and mean per cent sperm morphology (Kruger's) was 7.98. The 24‐h PT data, for 2 TW, showed mean motility 22.4%, mean total motile sperm count 13.7 × 106 and total motile sperm concentration 8.7 × 106/ml. Single patient had used the frozen spermatozoon for intrauterine insemination (IUI) of a surrogate mother resulting in birth of healthy newborn. It is concluded that poor PF and 24‐h PT semen quality is frequently seen among TW. As such, considerable proportion of TW should use more expensive method of ART, for example IVF/ICSI rather than inexpensive IUI.